2022
DOI: 10.1177/23779608221076821
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Beliefs of Nurses Regarding Antibiotic use and Prevention of Antibiotic Resistance

Abstract: Introduction Resistance to antibiotics is a threat confronting health care system worldwide. Nurses play a significant role in combating this threat. Objectives The present study examined the knowledge and attitude of nurses towards antibiotic use and prevention of antibiotic resistance. Methods The research involved a cross-sectional study conducted in a multi-cultural tertiary healthcare setting. The participants were 341 nurses. A structured self-administered questionnaire with a good validity and reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The dosage form affects the chemical reactions between the API and environment or compatibility of the API and excipient. There is usually no obvious visual or olfactory evidence of their occurrence [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage form affects the chemical reactions between the API and environment or compatibility of the API and excipient. There is usually no obvious visual or olfactory evidence of their occurrence [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, compounding is one of the competencies of a pharmacist [ 21 ]. Several studies have mentioned that pharmacists have higher awareness and knowledge of compounding than other healthcare workers [ 86 , 87 , 89 ], thus reducing the risk in the compounding process.…”
Section: Resultsmentioning
confidence: 99%
“…Most respondents assume that antibiotics cannot be given for viral diseases because they are cured automatically, and these results are good when we compare them with the results of a research conducted in Saudi Arabia, where (21.40%) of respondents think that viral infections are cured automatically. Due to a lack of awareness of the differences between viral and bacterial diseases, some respondents prefer taking antibiotics to treat all infections rather than treating the underlying cause (Alduraibi & Altowayan, 2022;Lalithabai et al, 2022;Rahman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The research result concluded that pharmacy students have superior knowledge of medication application than health sciences students. All health sciences students lacked the necessary mindset and application when it came to drug safety (Alduraibi & Altowayan, 2022;Wang et al, 2019;Lalithabai et al, 2022). The current study aims to determine students' knowledge about antibiotic utilization for upper respiratory tract infections in children.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses and healthcare workers have critical responsibilities to incorporate various AR prevention measures into their health education 4,25,62 such as adherence to treatment regimens, 16 proper handwashing, 63 avoiding antibiotic sharing, 20 and secure consultation and prescription from a physician, 64 as revealed in the findings. Setting up a more systematic and accurate monitoring and documentation system for AR in the clinical setting is essential for hospital administrators, doctors, and nurses to be aware of the prevalence of antibiotics in the clinical setting and respond appropriately to AR cases.…”
Section: Implications To Nursing Practicementioning
confidence: 96%